Beyond Macrophages and T Cells: B Cells and Immunoglobulins Determine the Fate of the Atherosclerotic Plaque - Mangge, Harald (Int J Mol Sci, 2020)
Atherosclerosis (AS) leading to myocardial infarction and stroke remains worldwide the main cause for mortality. Vulnerable atherosclerotic plaques are responsible for these life-threatening clinical endpoints. Atherosclerosis is a chronic, complex, inflammatory disease with interactions between metabolic dysfunction, dyslipidemia, disturbed microbiome, infectious triggers, vascular, and immune cells. Undoubtedly, the immune response is a most important piece of the pathological puzzle in AS. Although macrophages and T cells have been the focus of research in recent years, B cells producing antibodies and regulating T and natural killer (NKT) cell activation are more important than formerly thought. New results show that the B cells exert a prominent role with atherogenic and protective facets mediated by distinct B cell subsets and different immunoglobulin effects. These new insights come, amongst others, from observations of the effects of innovative B cell targeted therapies in autoimmune diseases like systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). These diseases associate with AS, and the beneficial side effects of B cell subset depleting (modifying) therapies on atherosclerotic concomitant disease, have been observed. Moreover, the CANTOS study (NCT01327846) showed impressive results of immune-mediated inflammation as a new promising target of action for the fight against atherosclerotic endpoints. This review will reflect the putative role of B cells in AS in an attempt to connect observations from animal models with the small spectrum of the thus far available human data. We will also discuss the clinical therapeutic potency of B cell modulations on the process of AS.